Spotlight on Mogamulizumab-Kpkc for Use in Adults with Relapsed or Refractory Mycosis Fungoides or Sézary Syndrome: Efficacy, Safety, and Patient Selection - Blackmon AL; Pinter-Brown L (Dove Medical Press, 2020)
Amanda L Blackmon,1 Lauren Pinter-Brown1,2 1Division of Hematology/Oncology, Department of Medicine, University of California, Irvine, Irvine, CA, USA; 2Chao Family Comprehensive Cancer Center, University of California, Irvine, Irvine, CA, USACorrespondence: Lauren Pinter-Brown Email lpinterb@uci.eduAbstract: Advanced cutaneous T cell lymphomas (CTCL) including mycosis fungoides (MF) and Sézary syndrome (SS) are often difficult to manage once they become resistant to initial systemic treatment. Current systemic treatments usually provide a limited duration of disease control, leaving this an area in desperate need of new treatment options for better long-term control. These conditions often affect the older population where transplantation may not be a feasible option. Recent studies evaluated a novel CCR4 humanized monoclonal antibody, mogamulizumab, in relapsed/refractory MF and SS, which show a meaningful progression free survival (PFS) benefit. In August 2018, mogamulizumab was approved by the FDA for the treatment of patients with relapsed/refractory MF/SS who have failed at least one treatment. Approval was based on the Phase III MAVORIC study comparing mogamulizumab to vorinostat, an FDA approved drug for this indication, in 372 patients. In this trial, mogamulizumab was found to have a superior PFS with a median of 7.7 months compared to 3.1 months in the vorinostat arm, with a hazard ratio of 0.53, p< 0.001. Mogamulizumab was well tolerated with the most common AE being infusion-related reactions (32%), drug rash (20%), diarrhea (23%), and fatigue (22%). We reviewed the literature leading to the development and approval of mogamulizumab and suggest which patients may benefit the most from this treatment.Keywords: CTCL, mycosis fungoides, Sézary syndrome, mogamulizumab, T cell lymphoma, CCR4